Reproduction of heifers sired by high or low residual feed intake angus bulls - E. Blair; Daniel W. Moser; T.T. Marston; Jennifer Bormann (Kansas Agricultural Experiment Station Research Reports, 2011)
Residual feed intake (RFI) has gained popularity as a selection tool for improving feed efficiency in beef cattle. RFI is the difference between what an animal consumes and what it is predicted to consume based on size and growth rate. Animals with low or negative RFI eat less than predicted and are more efficient. Although RFI is being used by the industry, research on the impact of selection for RFI on female fertility is lacking. The objective of this study is to evaluate the reproductive performance of heifers that have been selected for RFI.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen' s Day; 2011; Beef; Heifers; Residual feed intake; Bulls